2008
DOI: 10.1111/j.1529-8817.2008.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

ACCLIMATION TO LOW TEMPERATURE OF TWO ARTHROSPIRA PLATENSIS (CYANOBACTERIA) STRAINS INVOLVES DOWN‐REGULATION OF PSII AND IMPROVED RESISTANCE TO PHOTOINHIBITION1

Abstract: This study aimed to compare the ability of two Arthrospira platensis (Nordst.) Gomont strains, M2 and Kenya, isolated from two different habitats, to acclimate to low temperature (15°C). Both strains had similar growth rates at 30°C, but once acclimated to low temperature, M2 showed a greater decline in growth (59% vs. 41% in the Kenya strain). We suggest that the Kenya strain acclimated better to low temperature by down-regulating its photosynthetic activity through (i) decreasing antenna size and thus reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
2
15
2
Order By: Relevance
“…This has been proven also in laboratory experiments for some environmental factors such as irradiance (wu et al 2005;helBing et al 2006helBing et al ), temperature (gao et al 2008VonShaK & noVoplanSKy 2008) salinity (KeBeDe 1997) and alkaliphilic conditions (VonShaK & TomaSelli 2000). In our survey, its growth seemed however to be restricted to pH levels < 10.3.…”
Section: Resultsmentioning
confidence: 60%
“…This has been proven also in laboratory experiments for some environmental factors such as irradiance (wu et al 2005;helBing et al 2006helBing et al ), temperature (gao et al 2008VonShaK & noVoplanSKy 2008) salinity (KeBeDe 1997) and alkaliphilic conditions (VonShaK & TomaSelli 2000). In our survey, its growth seemed however to be restricted to pH levels < 10.3.…”
Section: Resultsmentioning
confidence: 60%
“…Lee-Feng et al [18] demonstrated that enhanced antioxidant enzyme activities at LT (15°C) are an efficient regulatory strategic response to LT-induced photoinhibition. In addition, a previous study also indicated that the adaptation of Arthrospira platensis to cold stress involves a down-regulation of photosynthetic activity and increased resistance to photoinhibition [19]. …”
Section: Introductionmentioning
confidence: 99%
“…), temperature (Gao et al. ; Vonshak and Novoplansky ), and salinity (Kebede ). So far, no extensive field studies exist that indicate whether these changes that have been observed under extreme laboratory situations also occur in nature.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse ecological strategies adopted by phytoplankton can be related to their morphological variability (Reynolds 1997); this acclimation value is directed toward adapting the best fitting trait to the prevailing environmental template (Naselli-Flores et al 2007). Morphological modification of A. fusiformis has been well studied under laboratory conditions such as variable irradiance (Wu et al 2005;Helbling et al 2006), temperature (Gao et al 2008;Vonshak and Novoplansky 2008), and salinity (Kebede 1997). So far, no extensive field studies exist that indicate whether these changes that have been observed under extreme laboratory situations also occur in nature.…”
Section: Discussionmentioning
confidence: 99%